TEACHING ITALIAN THROUGH VIRTUAL REALITY AND DIGITAL GAMES: FROM PREPARING BUCATINI TO SHOPPING AT THE PRATI MARKET. - CALABRETTA-SAJDER, RYAN; DEVICH, CLAUDIA (Annali d'Italianistica, 2025)
In this piece, we present theoretical and practical information used to incorporate Virtual Reality technology into the Italian curriculum at the University of Arkansas. We briefly discuss the "how" and "why" of Virtual Reality (VR) in the Italian program, demonstrating how VR permeates the language curriculum through a series of connected, task-based learning modules that incorporate authentic materials (places, spaces, language, and culture). We also analyze its successful integration, utilizing linguistic and cultural evidence (quantitative results), and explore the effect on students' learning and motivation (qualitative results). This contribution concludes with advice on how to adopt VR in a language curriculum. In addition, the advantages and disadvantages, including challenges concerning the adoption of VR will also be addressed. We will also share how VR can be used to address diversity, equity, and inclusion goals. In the end, student pre- and post-surveys and future directions for the project will be highlighted. We conclude that students learn as much, if not more, through the Virtual Reality setting and, afterwards, are also highly motivated to continue studying Italian on-campus and abroad.